2015
DOI: 10.1186/s12885-015-1017-3
|View full text |Cite
|
Sign up to set email alerts
|

Ewing sarcoma of the liver with multilocular cystic mass formation: a case report

Abstract: BackgroundEwing sarcoma is a rare tumor that occurs commonly in the long bones of children or adolescents that can also arise in soft tissues including the extremities, retroperitoneum, chest wall, and rarely in the liver as primary sites. We report a case of Ewing sarcoma arising primarily in the liver and, to our knowledge, this is the fourth reported case of Ewing sarcoma occurring in the liver.Case presentationA 27-year-old Japanese woman was admitted with sudden onset right upper abdominal pain. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…To the best of our knowledge there were four hepatic ES cases in English literature. [5][6][7][8] In our case she had multiloculated cystic liver lesion and diagnosed by CT scan and biopsy. In the English literature this was the second case of primary hepatic ES, which was presented with multiloculated liver cystic lesion.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…To the best of our knowledge there were four hepatic ES cases in English literature. [5][6][7][8] In our case she had multiloculated cystic liver lesion and diagnosed by CT scan and biopsy. In the English literature this was the second case of primary hepatic ES, which was presented with multiloculated liver cystic lesion.…”
Section: Discussionmentioning
confidence: 74%
“…Ozaki et al reported the first hepatic multiloculated cystic lesion diagnosed with hepatic ES. 7 In that case a 27-year-old Japanese woman was admitted with abdominal pain. Multiloculated cystic lesion on liver was revealed with clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…V literatuře se nejčastěji popisuje postižení ledvin, Zöllner et al evidují 152 případů [3], dále např. plic [4], žaludku [5], jater [6], urologických [7] či gynekologických orgánů.…”
Section: úVodunclassified
“…Extra skeletal cases are rare, and these patients generally present at an older age and demonstrate a greater overall 5-year survival than skeletal Ewing sarcoma tumours [14,15]. Reports of primary liver involvement have been noted, as well as gastrointestinal sites of origin, including the stomach, small intestine, and colorectal [16][17][18][19]. Nevertheless, ES is extremely rare in the small bowel.…”
Section: Introductionmentioning
confidence: 99%